2020
DOI: 10.3389/fneur.2020.590589
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cerebral Cavernous Malformations Presenting With Seizures: A Systematic Review and Meta-Analysis

Abstract: Background: Cerebral cavernous malformations (CCMs) presenting with seizures can be treated with neurosurgery or radiosurgery, but the ideal treatment remains unclear. Currently, there is no adequate randomized controlled trial comparing surgical treatment and radiotherapy for epileptogenic CCMs. Therefore, we conducted a systematic review and meta-analysis of available data from published literature to compare the efficacy and safety of neurosurgery and radiosurgery for epileptogenic CCMs. Methods: We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…[70][71][72] In a meta-analysis by Gao et al, 13.1% and 4.4% of patients with CCM experienced temporary and permanent neurological deficits after lesionectomy, respectively. 68 By comparison, only 9% of our CCM cohort experienced transient deficits and no patients experienced permanent deficits. One of the main concerns regarding MRgLITT of CCM is hemorrhage; however, only 1 of 32 patients (3.1%) in our study experienced postoperative hemorrhage, again reinforcing that MRgLITT may be a safe alternative to open resection with similar efficacy.…”
Section: Cerebral Cavernous Malformationsmentioning
confidence: 81%
See 1 more Smart Citation
“…[70][71][72] In a meta-analysis by Gao et al, 13.1% and 4.4% of patients with CCM experienced temporary and permanent neurological deficits after lesionectomy, respectively. 68 By comparison, only 9% of our CCM cohort experienced transient deficits and no patients experienced permanent deficits. One of the main concerns regarding MRgLITT of CCM is hemorrhage; however, only 1 of 32 patients (3.1%) in our study experienced postoperative hemorrhage, again reinforcing that MRgLITT may be a safe alternative to open resection with similar efficacy.…”
Section: Cerebral Cavernous Malformationsmentioning
confidence: 81%
“…Open microsurgical lesionectomy is considered the gold standard for treating DRE attributed to CCMs; however, the 78.1% seizure freedom rate with MRgLITT in this study compares favorably to open resection (70%-80%). [66][67][68] Given similar efficacy to open surgery, MRgLITT offers additional advantages of being minimally invasive and reducing microsurgical approach-related morbidity for deep-seated CCMs. MRgLITT may also be appealing for patients with multiple CCMs.…”
Section: Cerebral Cavernous Malformationsmentioning
confidence: 99%
“…Gao et al. [ 33 ] found that the seizure control rate was 79% for neurosurgery and 49% for radiosurgery. However, our total seizure control rate was 78.2% in these patients, who we followed as a single center.…”
Section: Discussionmentioning
confidence: 99%
“…These vessels lack muscular and elastic layers and are filled with blood at various stages of thrombosis and organization [ 6 , 7 ]. Sluggish blood flow through dysplastic channels results in recurrent thrombosis, calcification, and deposition of hemosiderin along the margins of the lesion [ 8 ].…”
Section: Introductionmentioning
confidence: 99%